“Mehnat ta’limini o’qitish metodikasi” fanini o`qitishda interfaol metodlardan foydalanish orqali ta`lim sifatini oshirish (SCIENCE and SOCIETY, 2017)
The article deals with interactive methods of teaching the subject "Methodology of teaching labor education" on the basis of mas- tering the theoretical knowledge of future teachers for the development of independent and creative thinking.